Customs, folk knowledge and production experience related to bee swarming in the Sarny region (according to expedition materials from the Sarny district of the Rivne region). - Dmytrenko , Alla (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the study. On the basis of field ethnographic materials collected in the Sarny district, analyze the phenomena of material culture, folk knowledge, archaic components of worldviews, customs and rites associated with bee swarming, and trace their features in forest and domestic beekeeping. Research methodology. Used historical methods (analysis and synthesis, typological, comparative-historical) and ethnological research method (collection of field materials according to the author's program-questionnaire, carried out using the bush method of ethnological research). Scientific novelty. For the first time in the Ukrainian ethnological literature, the ethnocultural features of the customs related to the swarming of bees in Sarny Polissia were investigated. Used expedition field materials collected by the author are being introduced into scientific circulation for the first time. Topicality. The topic of the article is relevant, as it reveals one of the aspects of custom and production experience associated with the development of beekeeping in Polissia, as an element of the National List of Intangible Cultural Heritage of Ukraine. Conclusions. It was found out that during the development of beekeeping in Sarny Polissia, a complex of worldviews, magical actions, customs, rites, folk knowledge, devices and production experience related to bee swarming was formed. Worldviews and associated magical actions were supposed to contribute to success in fishing. It has been proven that in forest beekeeping intervention in the process of swarming was minimal and was reduced to knowing the terms of swarming and observing it on the Green Holidays. During the period of domestic beekeeping, beekeepers began to actively intervene in all stages of the development of bees, which contributed to the formation of a system of knowledge, production experience and special devices.